EVALUASI PROGRAM PENDIDIKAN KARAKTER DI SMP ISLAM MATHOLI’UL FALAH BLORA PROVINSI JAWA TENGAH TAHUN 2021 - Ragowo Sandhi Lelono (Master of Public Administration, Universitas Slamet Riyadi, 2022)
Evaluation of the program to know the achievement of the programobjectives by knowing the implementation of program activities. Context, Input,Process, Product (CIPP) evaluation model is an easier model to understand andassess in terms of character education in schools that will be thorough as a whole. This study uses a qualitative method with data collection techniques throughinterviews and documentation on school residents. The results showed that thecharacter education program at Matholiuúl Falah Islamic Junior High School wasalmost entirely well run, the shortcomings occurred in the facilities andinfrastructure, few students were not disciplined. The evaluation of the charactereducation program at SMP Islam Matholi'ul Falah Blora, Central Java Province,has got good results in planting character values implemented, and internalizationor habituation of character education of each student conducting activities inschool. His advice is to improve the understanding and ability of school residentsfor character education in his school.Keywords: Program Evaluation, Character Building, Education.